Genome-wide characterization of the chitinase gene family in wild apple (Malus sieversii) and domesticated apple (Malus domestica) reveals its role in resistance to Valsa mali - Haxim, Yakupjan; Kahar, Gulnaz; Zhang, Xuechun; Si, Yu; Waheed, Abdul; Liu, Xiaojie; Wen, Xuejing; Li, Xiaoshuang; Zhang, Daoyuan (Frontiers in Plant Science, 2022)
Chitinases, type of hydrolase that responsible for catalyzing the hydrolysis of chitin, provide protection against plant fungal pathogens by degrading fungal chitin. Here, we identified chitinase gene family from wild apple (Malus sieversii) and domestic apple (Malus domestica) at genome-wide level and analyzed expression profile in response to Vals mali infection. A total of 36 and 47 chitinase genes belonging to glycosyl hydrolase 18 (GH18) and 19 (GH19) families were identified in M.sieversii and M.domestica genome respectively and classified into five classes based on their phylogenic relationship and conserved catalytic domains. These genes were randomly distributed across the chromosomes and expanded via both tandem and segmental duplication. The 8 of 36 MsChi genes and 17 of 47 MdChi genes were diﬀerentially expressed in response to V.mali. Furthermore, MsChi35 and its ortholog MdChi41, a class I chitinase, were constitutively expressed at high levels in the wild and domestic apple respectively and may play a crucial role in defense response against V.mali. Our results improve our understanding of chitinases family genes in two apple species and provide foundation for further studies of disease prevention in apple species.